Analisis Kelompok Usaha Peningkatan Pendapatan Keluarga Sejahtera di DKI Jakarta, 2014 - Simanjuntak, Menara (Bina Nusantara University, 2014)
This research aims to explore and find the determinant factors as it is important for the development of group UPPKS management in Jakarta Provincial through a qualitative descriptive approach. The number of respondents was limited for 2 groups that are still active in the Regional Municipality of East Jakarta in Pulogebang Village and West Jakarta in Kemanggisan Village. Research was conducted through in-depth interview with 2 officers and 2 members of the group; focus group discussion was followed by 8 members at each location. The findings of this study indicate that the lack of funds/start-up capital has not gained sufficient leverage; the absence of other sources of funding, in fact, almost all are individual business, so that managed such as savings and credit groups. Growing effort is being supported by additional capital that sought its own members, as well as the selection of profitable business activities. Group leader and members favored form of technical training, certain items are more salable. More individual businesses selling food and beverages are for their money-faster turnaround, rest handicraft products do not sell quickly, and thus this is the advantage of learning process through UPPKS. Recommendation for Jakarta Provincial Government is to make regulation and build relationship with Financial Institution to support the UPPKS.